Combination antiretroviral therapy (cART)-induced hippocampal disorders: Highlights on therapeutic potential of Naringenin and Quercetin. (June 2019) - Akang, Edidiong N.; Dosumu, Olufunke O.; Afolayan, Olasunmbo O.; Fagoroye, Adeola M.; Osiagwu, Daniel D.; Usman, Isilamiyat T.; Oremosu, Ademola A.; Akanmu, Alani S.
Highlights: Naringenin and Quercetin decrease ROS and potentiate enzymatic antioxidant production in the hippocampus. cART induced marked cytoplasmic shrinkage and several pyknotic nuclei in the dentate gyrus and cornus ammonis region. Naringenin and Quercetin attenuates cART-induced upregulation of monoamine oxidase-B expression in neurons. Naringenin and Quercetin also ameliorates cART-induced spatial memory impairments. Naringenin and Quercetin acted as effective antioxidants in vivo against cART-induced neurotoxicity. Abstract: Introduction: In spite of the multiple benefits of combination antiretroviral therapy (cART) on HIV positive patients, prolonged usage has been reported to exacerbate oxidative stress, and induce neurological and cognitive dysfunction, thus, the need to search for an adjuvant therapy to ameliorate the oxidative and improve treatment adherence with better virological outcome. This study aimed at determining the potential therapeutic effects of Quercetin and Naringenin on cART-induced cyto-architectural, neuro-behavioral and immunohistochemical changes in the hippocampus of the adult Wister rats. Materials and Methods: The animals were grouped as follows: Control, DMSO, 24 mg/kg cART (Tenovovir 300 mg, Lamivudine 300 mg and Efavirenz 600 mg), 50 mg/kg Naringenin, 50 mg/kg Quercetin, cART + Naringenin, cART + Quercetin were administered orally for 8 weeks. At the end of administration, neurobehavioural test was conducted, animals were euthanized and hippocampus was processed for oxidative stress markers, histology, TNF-α, and Monoamine oxidase-B expression. Results: At the end of 8 weeks of administration, 24 mg/kg cART decreased superoxide dismutase (SOD), catalase (CAT), reduced glutathione (GSH) and increased Malondialdehyde (MDA). Whereas, 50 mg/kg quercetin, and 50 mg/kg Naringenin decreased the oxidative stress (increased SOD, CAT, GSH, and reduced MDA) induced by cART (reduced SOD, CAT, GSH, and increased MDA). In addition, hematoxylin and eosin stained hippocampus showed that quercetin and naringenin prevented neurodegenerative changes (marked cytoplasmic shrinkage and several pyknotic nuclei in the dentate gyrus and cornus ammonis regions) in cART-treated rats. Furthermore, immunohistochemical studies revealed that quercetin and naringenin attenuates cART-induced upregulation of monoamine oxidase-B (MAO-B) expression. Likewise, from the Morris water maze neurobehavioral studies, naringenin and quercetin also ameliorated cART-induced memory impairments (initial spatial memory, reversal spatial memory and probe tests). Conclusion: This study shows that Naringenin and Quercetin have a good potential in reversing cART-induced hippocampal disorders in Wistar rats.